Doushantuo-Pertatataka—Like Acritarchs From the Late Ediacaran Bocaina Formation (Corumbá Group, Brazil) - Morais, L.; Fairchild, T. R.; Freitas, B. T.; Rudnitzki, I. D.; Silva, E. P.; Lahr, D.; Moreira, A. C.; Abrahão Filho, E. A.; Leme, J. M.; Trindade, R. I. F. (Frontiers in Earth Science, 2021)
Acritarchs, a polyphyletic group of acid-resistant organic-walled microfossils, dominate the eukaryotic microfossil record in the Proterozoic (2500–541 Ma) yet exhibit significant reduction in diversity and size at the transition to the Phanerozoic (541–520 Ma). Despite the difficulty of tracing phylogenetic relationships among acritarchs, changes in their complexity and diversity through time have allowed their use in paleoecological and biostratigraphic schemes. The Doushantuo-Pertatataka Ediacaran acritarch assemblage, for example, is usually considered as restricted to the early Ediacaran between 635 and 580 Ma. But similar, diverse acritarchs have been recovered from younger rocks in Mongolia and Arctic Siberia and are now reported here from phosphatized horizons of the upper Bocaina Formation (ca. 555 Ma), Corumbá Group, SW Brazil. In the overlying black limestones and shales of the latest Ediacaran Tamengo Formation (542 Ma) acritarch diversity is low, but the skeletal metazoans Cloudina and Corumbella are abundant. The Bocaina acritarch assemblage shares forms referable to the genera Leiosphaeridia, Tanarium, Asseserium and Megasphaera with the Doushantuo-Pertatataka assemblage, but also includes specimens similar to the Phanerozoic genus Archaeodiscina in addition to two new complex acritarchs. The first is covered by rounded low conical bumps, similar to Eotylotopalla but differs in having a distinct opening suggestive of greater (multicellular?) complexity. The second, identified here as Morphotype 1, is a double-walled acanthomorph acritarch with scattered cylindrical processes between the walls. The contrast in acritarch diversity and abundance between the Bocaina and Tamengo formations is likely due in part to paleoenvironmental and taphonomic differences (absence of the phosphatization window in the latter), as well as to the appearance of both suspension-feeding skeletal metazoans (Cloudina and Corumbella). The occurrence of Doushantuo-Pertatataka acritarchs in SW Brazil, northern Mongolia, and Arctic Siberia extend the biostratigraphic range of this assemblage up to the terminal Ediacaran Cloudina biozone.